Brazil’s Bolsa Familia and the Philippines’ “4Ps” CCT Programs: Considering South–South Cooperation for Social Protection - Curry, Mark Stevenson (Animo Repository, 2013)
Conditional Cash Transfer (CCT) programs were developed in the mid to late 1990s in Mexico and Brazil in response to the economic upheavals that affected the poor and vulnerable in Latin America following the imposition of structural adjustment policies. These social protection programs provide immediate cash disbursements under beneficiary compliance with health and education requirements, particularly for children and mothers. Since then, CCT programs have been implemented throughout Latin America and are rapidly being introduced in Africa and Asia, including the Philippines. Since the mid 2000s, the World Bank and other international financial institutions have been significantly involved in the implementation and scholarship of such programs as part of newly instituted social protection objectives. This introduces a formidable factor of Northern management and Southern implementation. In this way, CCT projects tend to follow a formula and exhibit many similar aspects of design, objectives, and evaluation measures. However, Brazil’s CCT program directly addressed social problems introduced by earlier neoliberal policy making and falls under a single centralized authority. The Philippine program has multiple institutional stakeholders and was introduced in 2007 under an expressly neoliberal presidency. By considering the similarities and differences in the cases of Brazil’s Bolsa Familia and the Philippines’ 4Ps, the mediation of the World Bank and other development lenders can be differently construed. There exists a potential for direct South–South, peer–peer correspondence of experience, cooperation, and autonomous development practices within terms that Boaventura de Souza Santos describes as an “epistemology of the South.” This alternate perspective on CCT progress and social protection in general has not until now been examined.